The role of the platelets in inflammation - Śliwińska-Stańczyk, Paula (Reumatologia/Rheumatology, 2005)
Platelets are the rich source of potent inflammatory factors and the key element linking the processes of hemostasis and inflammation. Platelets are activating in patients with rheumatoid arthritis. This activation contributes to development of the clinical symptoms.